2012
DOI: 10.1155/2012/642187
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Health Beliefs among Saudi Women

Abstract: Background. Physical activity (PA) is associated with health benefits and disease prevention and is often prescribed in managing many health conditions. Understanding the cultural influences is relevant in order to effectively promote PA. The objective of this study was to assess the level of PA among Saudi women, measured by daily step count, and the association between PA and health beliefs. Methods. A total of 161 eligible participants were asked to complete two questionnaires to assess health beliefs: Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 45 publications
(46 reference statements)
0
52
1
Order By: Relevance
“…During the last few decades, adult Saudi had enjoyed the modern Western civilization but at the same time had progressively suffered from its disadvantage; obesity and inactivity. Several Saudi studies reported increases in the percentage of adult Saudis with low PAL [2]-[5] [20]. Need to investigate the relationship between PAL and HRQoL was raised by the above mentioned facts.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few decades, adult Saudi had enjoyed the modern Western civilization but at the same time had progressively suffered from its disadvantage; obesity and inactivity. Several Saudi studies reported increases in the percentage of adult Saudis with low PAL [2]-[5] [20]. Need to investigate the relationship between PAL and HRQoL was raised by the above mentioned facts.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, great changes in physical activity and eating habits have occurred in our society and low levels of physical activity and sedentary living are becoming increasingly prevalent among the Saudi children [13]. Overweight and obesity is becoming a public health concern among Saudi population of all ages [5,[14][15][16]. Moreover, with massive urbanization and increased reliance on computer and telecommunication technology, further reductions in physical activity are projected for the coming years [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that different cultural beliefs influence various health outcomes. Social and cultural influences play a major role in promoting physical activity [15]. The majority of children and teen do not meet the current guidelines suggested by experts of a minimum of 60 minutes duration of moderate to vigorous physical activity per day [18].…”
Section: Introductionmentioning
confidence: 99%
“…Saudi Arabia, considered a rapidly developing country, faces progressive urbanization and the fast adoption of a western lifestyle contributing to rise CVD burden [17]. Significant proportion among younger aged population is at increased risk for the development of hard coronary heart events [3,18].…”
Section: Discussionmentioning
confidence: 99%